ANALYSIS OF THE PERSPECTIVES OF NEUROMARKETING RESEARCH OF CONSUMER BEHAVIOR - Grigoryan, Shushanna (Modern Psychology, 2022)
This theoretical article discusses the historical overview, essence and features of neuromarketing as a development of science. The categorical system and toolkit of neuromarketing research as a new field of science, which originated at the border of biology, medicine, economics, sociology and psychology, has been studied. Accordingly, the purpose of this article is to comprehensively present neuromarketing as a new direction in the study of consumer psychology. The need to use neuromarketing methods to identify the needs of consumers is becoming more and more important, as in the modern world consumers are overloaded with advertising messages, the competition between "advertisers" is intensifying. That is why marketers need to develop effective marketing messages that will affect a person's subconscious, motivating him, for example, to buy a product or use a service. In this sense, neuromarketing is apparently a research tool that measures a person's subconscious reactions to marketing incentives. The article critically analyzes the existing methods of neuromarketing, reveals th,eir advantages and disadvantages. As a result, the following groups of neuromarketing methods were identified: methods for measuring the metabolic activity of the brain; Methods that measure the electrical activity of the brain, methods for measuring subconscious reactions. These methods make it possible to assess the level of attention and emotional involvement, activation of memory.Excessive number of brands in the market leads to information overload. The urbanization of modern society creates an environment where too many shops offer similar products. This is why it is important to study the methods of neuroscience to determine whether marketing choices lead to maximum satisfaction of consumer needs. Neuromarketing, as a scientific concept in the field of marketing research, aims to study, understand and analyze consumer behavior. As a combination of two disciplines, Consumer Neuroscience and Neuroscience, Neuromarketing replaces traditional types of marketing research.
Keywords: Neuromarketing; , Subconscious; Consumer; Consumer Behavior; Marketing Signals